CLIMATE CHANGE AND ITS IMPACT ON WOMEN’S POLITICAL, SOCIAL, AND ECONOMIC LIVES IN PAKISTAN WITH ASSOCIATED CHALLENGES - Rana Ali Hassan (International Journal of Contemporary Issues in Social Sciences, 2024)
Climate change is the environmental issue in Pakistan that affected her in many key areas; Pakistan face challenges like floods, droughts and extreme heatwave due to global warming. The victims in Pakistan are both genders but the women is struggling a lot due to climate change their social, political and economic life has been disturbed whether the women is rural or urban. Women’s face challenges of economical and socially as well as their health issues and the women harassment are also a critical issue that generates due to climate change during disasters and post-disaster time period. The research is conducted to highlight the gender discrimination due to climate change and drastic measures that should be taken to overcome the problem. The research employs a secondary source and descriptive technique to comprehensively understand the effects of climate change on women. A qualitative method technique analysis is used to utilised to identify and elucidate crucial key findings.